(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of unexplained physical symptoms in 5-15 years old children and its association with emotional disorder in psychiatric clinic of a public sector hospital. Study Design: Cross-sectional descriptive study Place and Duration of Study: This study was conducted in the Department of Paediatric OPD, DIMC, DUHS, Karachi from January 2015 to June 2015. Materials and Methods: 144 samples of 5-15 years old children of both genders with somatic /physical symptoms fulfilling the inclusion criteria which were referred to the Psychiatry clinic. Semi structured questionnaire based on Urdu version of SDQ parent version were filled by the parents to assess the emotional problems in these children. Results: Analyses were completed for sample of 135 patients. 9 were excluded due to incomplete questionnaire. The mean age of children was 10.95 years. Pain predominated as physical symptoms in 5-10 years age group was pain, it included abdominal pain, headaches, limb pain, backache, chest pain. Fatigue, difficulty in breathing tremors, jerky movement and nausea and vomiting were more common in females. Anxiety disorder n=51 (50%), depression n=28 (28%), and somatoform disorder n=22 (22%) were the psychiatric comorbidities observed in these children. Conclusion: Children presenting with unexplained medical symptoms are often not managed appropriately by the Pediatricians due to lack of awareness. Majority of children presenting with MUS suffer from emotional disorders.